2014
DOI: 10.1021/jp5012318
|View full text |Cite
|
Sign up to set email alerts
|

Electron Transport Properties of Au, Ag, and Cu Atomic Contacts in a Hydrogen Environment

Abstract: This study investigates the electron transport properties of Au, Ag and Cu atomic contacts in a hydrogen environment at 10 K, by using the mechanically controllable break junction (MCBJ) technique. A sharp 0.2 G 0 (2e 2 /h) peak was observed in the conductance histogram of H 2 /Cu contacts, whereas a low conductance tail (<1 G 0 ) was observed with H 2 /Au contacts. The conductance behavior of the Ag contacts was found not to change by the introduction of hydrogen, thus, indicating a weak interaction between h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 33 publications
2
25
0
Order By: Relevance
“…When the distance between the second-topmost surface layers of the Au-H 2 -Au junction is set to 22.0Å (the distance between the electrodes is arbitrary, since in real experiments, it is set by the break junction setup) [38][39][40][41][42], the equilibrium distance between the electrodes' topmost layers is optimized to 17.82Å, and the conductance is 0.74G 0 , in agreement with Ref. [43].…”
Section: Resultssupporting
confidence: 70%
“…When the distance between the second-topmost surface layers of the Au-H 2 -Au junction is set to 22.0Å (the distance between the electrodes is arbitrary, since in real experiments, it is set by the break junction setup) [38][39][40][41][42], the equilibrium distance between the electrodes' topmost layers is optimized to 17.82Å, and the conductance is 0.74G 0 , in agreement with Ref. [43].…”
Section: Resultssupporting
confidence: 70%
“…The other strong signals found at ±17 meV for H 2 in the IETS spectrum are due to conformational switching of the molecule in the tunnel junction. [11][12][13][14][15][16][17][18][19][20][21] As previously mentioned, the energy of the switching is extremely sensitive to coverage, tip state, and tipsurface separation. [17][18][19][20][21] There are also inelastic peaks around ±4 meV for H 2 .…”
mentioning
confidence: 91%
“…[22,23] This was the first demonstration of H 2 rotational spectra on a bare metal surface by IETS, which raises the question of what makes Au(110) a more suitable substrate than Cu(111), [ 17,18] Ag(111), [19] or nanojunctions made of various metals. [9][10][11][12][13][14][15][16] It is also unclear if rotational IETS probes single molecules or molecular ensembles.…”
mentioning
confidence: 99%
“…5 Afterward, considerable efforts have been devoted to the study of single hydrogen molecular junctions with coinage metal electrodes due to their much easier applications in molecular electronics. [6][7][8][9][10][11][12][13][14][15] However, most of these studies focused on Au/H 2 junctions, while only a few works have been reported for Ag and Cu atomic contacts, because a) Author to whom correspondence should be addressed. Electronic mail:…”
Section: Introductionmentioning
confidence: 99%